Clinical Value of NT-proBNP and Lactate Parameters in Infants with Congenital Heart Defects - Narmin Akif Azizova (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Congenital heart disease (CHD) is one of the most common anomalies worldwide, defined as an anatomical abnormality of the heart and/or great vessels. The aim of review is to find out whether this marker is diagnostically important in detecting and determining the severity of the disease, based on the analysis of NT-proBNP indicators of patients admitted with congenital heart defects under the age of 1 year, and also to check whether there is a correlation between lactate and NT-proBNP among patients with congenital heart defects. In the result NT-proBNP values in 81 critical condition congenital anomaly patients averaged 12811.6±810.7 (445-40163), control group averaged 135.6±14.0 (78-320) among 20 patients, Pf < 0.001 which was reported to be statistically significant. In our study, NT-proBNP indicators of patients diagnosed with CHD were found to be higher in the first 28 days compared to other infant groups (1-6 months and 6-12 months). The results revealed that the difference between the CHD lactate level between the surviving and lethal groups was statistically significant (Pf< 0.001; Pu 0.017). In conclusion, we should state that in our study, blood NT-ProBNP levels in critically ill infants with congenital heart anomalies were found to be approximately 10 times higher than in healthy infants (Pf < 0.001). At the same time, a correlation was established between the blood lactate index and the blood NT-ProBNP level.